Emission regulation: Prices, quantities and hybrids with endogenous technology choice - Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2023)
This paper examines the investment incentives of market-based regulation, with focus on the technology characteristics the different regulatory schemes tend to incentivize. The firms' technology choice is socially optimal if and only if the aggregate emission allowance supply is completely inelastic. Further, in the presence of uncertainty, elastic emission allowance supply and strictly convex environmental damage, it is optimal to tax investment in technologies that induce large variance in emissions. Last, price elastic supply of emission allowances may increase the volatility in the product market, depending on the risk environment the firms face. The results indicate that introduction of permit price stabilizing measures in an emission trading system will come at the cost of suboptimal technology investments. It may also cause increased fluctuations in product prices.
Keywords: Q52; Q58; D81; H41; 330; Regulation; technology choice; uncertainty; investment; welfare